2017
DOI: 10.1093/inthealth/ihx021
|View full text |Cite
|
Sign up to set email alerts
|

Journey towards universal viral load monitoring in Maputo, Mozambique: many gaps, but encouraging signs

Abstract: IntroductionViral load (VL) monitoring for people on antiretroviral therapy (ART) is extremely challenging in resource-limited settings. We assessed the VL testing scale-up in six Médecins Sans Frontières supported health centres in Maputo, Mozambique, during 2014–15.MethodsIn a retrospective cohort study, routine programme data were used to describe VL testing uptake and results, and multi-variate logistical regression to estimate predictors of VL testing uptake and suppression.ResultsUptake of a first VL tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
(29 reference statements)
7
32
1
Order By: Relevance
“…Even when high VL-testing coverage is achieved, good HIV treatment outcomes will remain out of reach if effective follow-up of suspected failure patients does not occur. Our follow-up testing rate among suspected failures (83%) was similar to recent findings in Lesotho (85%) and notably higher than rates reported previously in Swaziland (70%), Malawi (30%), Mozambique (35%) or Siaya County, Kenya (35%), [17,50,51,[53][54][55]. Notably, less than one-third of suspect failures had a suppressed VL at their first follow-up test, likely corresponding to high levels of acquired first-line drug resistance in this mature cohort where VL-monitoring was only recently introduced, as reported in similar settings [17,25,34,35,50,54,56,57].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Even when high VL-testing coverage is achieved, good HIV treatment outcomes will remain out of reach if effective follow-up of suspected failure patients does not occur. Our follow-up testing rate among suspected failures (83%) was similar to recent findings in Lesotho (85%) and notably higher than rates reported previously in Swaziland (70%), Malawi (30%), Mozambique (35%) or Siaya County, Kenya (35%), [17,50,51,[53][54][55]. Notably, less than one-third of suspect failures had a suppressed VL at their first follow-up test, likely corresponding to high levels of acquired first-line drug resistance in this mature cohort where VL-monitoring was only recently introduced, as reported in similar settings [17,25,34,35,50,54,56,57].…”
Section: Discussionsupporting
confidence: 89%
“…Notably, a recent clinical trial reported higher rates of retention, VL-suppression and referral to decentralized care in patients who received POC-VL-testing [66]. Yet, our findings (and others [17,50,53,54,56]) indicate that providing access to the technology is not enough. Regular staff training, mentoring and VL "focal-points" who monitor testing protocols are recommended.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The uptake of routine VL monitoring among the patients ranged from 3% to 95% in seven sub-Saharan countries 10. Studies reported that there were individual and programme level factors which influenced the uptake of VL testing by the patients 11 12…”
Section: Introductionmentioning
confidence: 99%